PENGARUH EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI SULAWESI SELATAN PADA TAHUN 2010-2012 - Badaruddin Badaruddin (AkMen JURNAL ILMIAH, 2015)
The success of development characterized by high economic growth. Economic growth is expected to improve factors - factors of production, which stimulates economic development on a large scale. This study aims to determine how much influence these variable exports for economic growth in South Sulawesi using several theories and the results of previous research on economic growth. Variables examined exports using time series data for the period 2010 - 2012 and analyzed using Ordinary Least Square method. The study found that government spending variable exports have a positive and significant impact on economic growth.